Hard and Soft Euroscepticism in the European Parliament. (6th February 2022) - Kaniok, Petr; Komínková, Magda
Abstract : Euroscepticism has become a stable component of the European Parliament. But is there one distinct Euroscepticism in the European Parliament or do various types exist there? Departing from the widely accepted definitions of hard and soft Euroscepticism, we analysed the behaviour of Eurosceptical groups in the European Parliament in order to assess how they differ. Using data from parliamentary questions, we argue that there are substantial differences between these two groups. This suggests that hard and soft Euroscepticisms do not represent different degrees of one phenomenon, but instead refer to two fundamentally different stances towards European integration.